PENGARUH KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA KARYAWAN DI CV SINAR PASUNDAN) - Sipa Sopiatunnisa; Adi Muhammad Nur Ihsan (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This causal quantitative study aims to evaluate how financial compensation impacts production workers' job satisfaction at CV Sinar Pasundan, utilizing work motivation as a mediating factor. The methodology employs a census approach through total sampling, collecting primary data via questionnaires analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The findings indicate that monetary rewards do not directly enhance job satisfaction. However, financial incentives significantly bolster work motivation, which subsequently serves as the primary driver for job satisfaction. The study concludes that work motivation functions as a complete mediator, demonstrating that financial adjustments fail to automatically generate job satisfaction unless they successfully transform into psychological stimuli first to maintain enterprise operational stability.